Meningkatkan Hasil Belajar Matematika Siswa Melalui Model Kooperatif Tipe NHT Berbantuan Media Berbasis Augmented Reality Pada Materi Kubus dan Balok - Indagita Cahyani Sero Sero; Nursiya Bito; Bertu Rianto Takaendengan (Jambura Journal of Mathematics Education, 2026)
This study aims to improve students' mathematics learning outcomes in the topic of flat-sided solid shapes, specifically cubes and cuboids, through the application of the Numbered Heads Together (NHT) cooperative learning model combined with Augmented Reality (AR)-based learning media. The study used Action Research (CAR) based on the Kemmis and Mc. Taggart model, implemented in two cycles. Observations showed significant improvements in various aspects of learning. Teacher and student activities, initially in the Fair (CB) category, improved to Good (B) and Very Good (SB) categories. In the affective and psychomotor domains, the attitude and skills assessment results showed improvements from Fair (CB) to Good (B) and Very Good (SB). Meanwhile, cognitive learning outcomes obtained through written tests increased from 69.23% to 84.62%, indicating that most students had met the learning objectives. Thus, all assessment aspects had achieved success indicators in cycle II through the implementation of the Numbered Heads Together (NHT) cooperative learning model assisted by Augmented Reality-based learning media.